Ameloblastic carcinoma - Praveen B Kumar; Vaishali Keluskar; Anjana S Bagewadi; Arvind Shetti; Raghavendra Byakodi (Wolters Kluwer Medknow Publications, 2009)
Ameloblastoma of jaws are common and locally destructive tumors originating from odontogenic apparatus. They constitute approximately 1% of all jaw tumors with 80% occurring in the mandible. Ameloblastoma exhibiting a frank malignancy is a rare entity and occurs in less than 1% of all ameloblastomas. Among the two jaws, ameloblastic carcinoma involving maxilla is extremely rare with only few cases reported so far in the literature. Here we report two cases of ameloblastic carcinoma one involving the maxilla and the other involving mandible, with an aggressive clinical course leading to extensive local destruction of the affected jaws.